CIITA Leucine-Rich Repeats Control Nuclear Localization, In Vivo Recruitment to the Major Histocompatibility Complex (MHC) Class II Enhanceosome, and MHC Class II Gene Transactivation - Hake, Sandra B. (American Society for Microbiology, 2000)
The major histocompatibility complex (MHC) class II transactivator CIITA plays a pivotal role in the control of the cellular immune response through the quantitative regulation of MHC class II expression. We have analyzed a region of CIITA with similarity to leucine-rich repeats (LRRs). CIITA LRR alanine mutations abolish both the transactivation capacity of full-length CIITA and the dominant-negative phenotype of CIITA mutants with N-terminal deletions. We demonstrate direct interaction of CIITA with the MHC class II promoter binding protein RFX5 and could also detect novel interactions with RFXANK, NF-YB, and -YC. However, none of these interactions is influenced by CIITA LRR mutagenesis. On the other hand, chromatin immunoprecipitation shows that in vivo binding of CIITA to the MHC class II promoter is dependent on LRR integrity. LRR mutations lead to an impaired nuclear localization of CIITA, indicating that a major function of the CIITA LRRs is in nucleocytoplasmic translocation. There is, however, evidence that the CIITA LRRs are also involved more directly in MHC class II gene transactivation. CIITA interacts with a novel protein of 33 kDa in a manner sensitive to LRR mutagenesis. CIITA is therefore imported into the nucleus by an LRR-dependent mechanism, where it activates transcription through multiple protein-protein interactions with the MHC class II promoter binding complex.